Política e espaço urbano: controvérsias e definições da política urbana em Goiânia - RODRIGUES, Juliano Martins (2008)
In this dissertation we themed the urban policy in the country through the changes restored since the 1988 Constitution and the adoption of the Statute of the City in 2001, with main focus on the strengthening of the municipal level. We understand the urban policy as a social construction able to comprehend a set of social, economic, political and cultural dynamics in the city, therefore directly linked of socio-space organization of cities, such as Goiania. The adopted approach was especially based on theoretical and conceptual propositions of Henri Lefebvre, which think the social problems of the city at the center of the determinations of urban policy and the social production of space. For this conception we articulate the understanding derived of Pierre Bourdieu s concepts, who had taken the city as a symbolic sphere of production, which the coexistence of speeches, interests, conflicts and consensuses answer for the elaboration of instruments of planning and urban management. The study focused on empirical analysis, based at the confluence of urban reform with the development of the Managing Plan of Goiania, approved in 2007. Through this appreciation we could understand the logic and the mechanisms to convert the instruments of control of the occupation and use of land in a field of struggle, which the actors shape social interests, strategies and speeches that define them as political agents in the city.